VACCINATION: RECOMMENDATIONS FOR PHYSICIANS AND PARENTS - M.I. Ivardava (Union of pediatricians of Russia, 2011)
The introduction of mass immunization programs in public health care separated in time the period of infectious diseases in pre-and post-vaccination era. To date, it is clear that there is no more effective preventive programs in medicine, than vaccination. Unfortunately,  at present, the number of unjustified refusals of vaccinations increased that are associated with anti-vaccination parents mood. This article is intended for pediatricians, who often face in their practice with the questions of parents about vaccination and its pros and cons. We'll try to answer the most pressing of them and dispel some misconceptions and myths related to infectious diseasesprevention. Key words: vaccination, childhood infections, mandatory vaccinations, complications, the immune system. (Pediatric pharmacology. - 2011; 8 (6): 128-131).